2020
DOI: 10.3892/wasj.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

Role of laparoscopic simulators in the development and assessment of laparoscopic surgical skills in laparoscopic surgery and gynecology (Review)

Abstract: The aim of the present review article was to provide an overview of the evaluation and capability of the different types of laparoscopic simulators in the application of training in laparoscopic gynecological surgery. The literature suggests that the acquisition of surgical psychomotor skills is best achieved in a simulated laboratory outside of the live operating environment. The present review article includes scientific publications on current laparoscopic gynecological simulators, including laparoscopic bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 120 publications
0
11
0
1
Order By: Relevance
“…Low-fidelity models have been used in gynaecology for some time [ 67 ]. More advanced models have been developed in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…Low-fidelity models have been used in gynaecology for some time [ 67 ]. More advanced models have been developed in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…In a review article, we provided an overview of the evaluation and capacity of the different types of laparoscopic simulators including laparoscopic box trainers, laparoscopic VR simulators, animal models, human cadavers and lightly embalmed human cadavers in the development and assessment of training in laparoscopic gynecologic procedures. We suggested that the clinical training curriculum of obstetrician-gynecologists should include laparoscopic VR simulators through a simulation-based education program outside the live operative environment under appropriated supervision in order to ensure the acquisition of maximal surgical psychomotor skills and the achievement of high-quality laparoscopic training [35]. Moreover, Papanikolaou et al suggested that teaching hospitals should introduce training programs using laparoscopic simulators with standardized and reproducible tasks in order to achieve better patient care with safety, efficiency and lower cost [36].…”
Section: Discussionmentioning
confidence: 99%
“…A digital camera provides video output to a monitor on which the trainees watch their own movements while performing the teaching task. [ 7 ] A box trainer utilizing the camera, screen, light source, and endoscopic instruments enables developing laparoscopy skills. Laparoscopy instruments: Atraumatic grasping forceps (both jaw opening), grasping forceps curved left (both jaw opening-Maryland Dissector), scissors curved left (both blades opening-Metzenbaum), and modular needle holder.…”
Section: Methodsmentioning
confidence: 99%
“…A digital camera provides video output to a monitor on which the trainees watch their own movements while performing the teaching task. [ 7 ] A box trainer utilizing the camera, screen, light source, and endoscopic instruments enables developing laparoscopy skills.…”
Section: Methodsmentioning
confidence: 99%